Association of plasma lactoferrin levels with disease severity in glaucoma patients - Wang, Zuo; Liu, Donghua; Yuan, Hang; Li, An; Wang, Jinxia; Zhu, Xiong; Xiu, Wenbo; Zhang, Gao; Chen, Yang; Chen, Lingling; Xiao, Xiao; He, Chong; et al. (Frontiers in Medicine, 2024)
Objective: To explore the relationship between plasma lactoferrin(Lf) and glaucoma, assessing the clinical utility of Lf in glaucoma.A cross-sectional study involved 161 glaucoma patients and 115 healthy controls, with a follow-up of 14 subjects after approximately 2 years. Plasma Lf markers were quantified using ELISA, comparing levels between glaucoma patients and healthy controls, and analyzing plasma Lf across different glaucoma severity grades.Results: Glaucoma patients had significantly elevated plasma Lf levels compared to healthy controls (p <0.001). Higher plasma Lf levels correlated with more severe disease stages (H-P-A grades showed r = 0.435, p < 0.001; AGIS grades showed r = 0.436, p < 0.001) and reduced Retinal Nerve Fiber Layer (RNFL) thickness (RNFL thickness showed r = -0.204, p = 0.024). ROC curve analysis demonstrated the efficacy of glaucoma markers in differentiating early-stage from advanced glaucoma.Plasma Lf levels are significantly associated with glaucoma severity and may be involved in the pathogenic progression of the disease.